Pengaruh Pola Pemasangan dan Rasio Dimensi Propeller Terhadap Unjuk Kerja Perahu Tipe Penggerak Contra Rotation Propeller - Fasrul Anugrah; Ikhwanul Qiram; Anas Mukhtar (Virtual of Mechanical Engineering Article, 2021)
The propeller is an important part of the ship's propulsion installation. Differences in propeller design can affect the propulsion performance of the ship. This study aims to determine the effect of variations in dimension ratio and propeller installation pattern on the performance of the contra rotation propeller type boat. The research was carried out experimentally by using variations of three-dimensional propeller ratios including R1 (1:1); R2 (1:1/2) and R3 (1:1/4), while the pattern of placement of the shaft tilt angle includes 15oand 20o. The flow pattern is conditioned with the waveless and wavy flow. Data collection includes boat speed and visualization of fluid flow behind the propeller which is then analyzed to obtain performance characteristics for each variation used. The results showed that the dimension ratio and the pattern of contra rotation propeller installation affected the speed and thrust of the boat, where the optimum power was obtained at the variation of the ratio R2 at a shaft tilt angle of 15owith the provision of a water flow mechanism without waves resulting in a speed of 0.576923 cm/second and under conditions of wavy at 0.523256 cm/second. The greatest thrust occurs in conditions of water flow without waves at the variation of the ratio R2 with a value of 33.23 kN and in wavy conditions of 30.13 kN. Visualization of fluid flow behind the shaft has shown the performance of the contra rotation propeller in various variations given through changes in the shape and length of the resulting path .Keywords: dimension ratio, installation pattern, contra rotation propeller, boat performance